Desired Sterilization Procedure at the Time of Cesarean Delivery According to Insurance Status. Issue 6 (December 2019) - Morris, Jane; Ascha, Mustafa; Wilkinson, Barbara; Verbus, Emily; Montague, Mary; Mercer, Brian M.; Arora, Kavita Shah
Abstract : OBJECTIVE: To evaluate whether women with Medicaid are less likely than their privately insured counterparts to receive a desired sterilization procedure at the time of cesarean delivery. METHODS: This is a secondary analysis of a single-center retrospective cohort examining 8, 654 postpartum women from 2012 to 2014, of whom 2, 205 (25.5%) underwent cesarean delivery. Insurance was analyzed as Medicaid compared with private insurance. The primary outcome was sterilization at the time of cesarean delivery. Reason for sterilization noncompletion and Medicaid sterilization consent form validity were recorded. Secondary outcomes included postpartum visit attendance, outpatient postpartum sterilization, and subsequent pregnancy within 365 days of delivery. RESULTS: Of the 481 women included in this analysis, 78 of 86 (90.7%) women with private insurance and 306 of 395 (77.4%) women with Medicaid desiring sterilization obtained sterilization at the time of cesarean delivery (relative risk 0.85, 95% CI 0.78–0.94). After multivariable logistic regression, gestational age at delivery (1.02 [1.00–1.03]), adequacy of prenatal care (1.30 [1.18–1.43]), and marital status (1.09 [1.01–1.19]) were associated with achievement of sterilization at the time of cesarean delivery. Sixty-four (66.0%) women who desired but did not receive sterilization at the time of cesarean delivery did not have valid, signed Medicaid sterilization forms, and 10 (10.3%) sterilizations were not able to be completed at the time of surgery owing to adhesions. Sterilization during cesarean delivery was not associated with less frequent postpartum visit attendance for either the Medicaid or privately insured population. Rates of outpatient postpartum sterilization were similar among those with Medicaid compared with private insurance. Among patients who did not receive sterilization at the time of delivery, 15 patients (each with Medicaid) had a subsequent pregnancy within the study period. CONCLUSION: Women with Medicaid insurance received sterilization at the time of cesarean delivery less frequently than privately insured counterparts, most commonly due to the absence of a valid Medicaid sterilization consent form as well as adhesive disease. The constraints surrounding the Medicaid form serve as a significant barrier to achieving desired sterilization. Abstract : Women with Medicaid insurance receive desired sterilization less frequently than their privately insured counterparts at the time of cesarean delivery.